The effect of product quality and price on mask purchase decisions mediated by promotion at pt. wom finance int the jabodebek area - Prasetya, Budi; Haryono, Budi (Enrichment : Journal of Management, 2025)
Making money, investing wisely, and saving are inseparable parts of human life, regardless of how rich or poor they are (Kotler & Keller in Aprila, Born N., 2021). Gold is one of the most popular investment instruments for Indonesian society amidst the unstable currency values, as investing in gold is considered to have relatively safe value from inflation and is also a liquid product that can be easily resold. In the midst of the phenomenon where many people are returning to invest in gold, MasKu product in Jabodebek Area has never reached its annual financing targets, although financing has consistently increased. Hence, there is a need for efforts to boost sales to encourage profit growth. This research aims to determine the effect of promotion in mediating the influence of product quality and price on the purchasing decisions of MasKu product in Jabodebek Area. Population in this study was all consumers of MasKu product who live in the Jabodebek Area, with a sample size of 105 respondents. Data was obtained through a questionnaire in the form of google form distributed via WhatsApp blasts to consumers in the Jabodebek Area. The data analysis technique used SmartPLS 4.1. From the analysis results, it was found that product quality and price each have a significant positive effect on purchasing decisions. Product quality and price each have a significant positive effect on promotion. Promotion has a significant positive effect on purchasing decisions. Promotion significantly positively mediates the effect of product quality on purchasing decisions, and promotion significantly positively mediates the effect of price on purchasing decisions.